(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Religious freedom in Greater Romania. Constitutional and Legislative Provisions The Great Union has formed Greater Romania, but provoked new analysis and debates regarding freedom of religion, in the context of different legislation of the geographical areas joined with the Kingdom of Romania. Therefore, after a brief presentation of the way Greater Romania was established, the author emphasizes the religious freedom regulations in the 1923 Constitution of Romania and the 1928 Law of Cults.